Some Estimates for the Fourier Transform on Rank 1 Symmetric Spaces (Analysis in Theory and Applications, 2018)
Two estimates useful in applications are proved for the Fourier transform inthe space $\rm{L}^2(\rm{X})$, where $\rm{X}$ a symmetric space, as applied to some classes of functionscharacterized by a generalized modulus of continuity.
Keywords: Fourier transform; generalized continuity modulus; symmetric space.